Pengaruh Konsumsi, Utang Negara, Dan Total Penerimaan Zakat Terhadap Perekonomian Indonesia - Irfan Musyaffa; Neli Aida; Asih Murwiati; Arivina Ratih; Heru Wahyudi (Journal on Education, 2022)
This study aims to find out how 1) household consumption, 2) state debt, 3) and zakat receipts influence Indonesia's gross domestic product. The data in this study is secondary data obtained from the official website of the Ministry of Finance, the National Amil Zakat Agency and the Indonesian Statistics Center with a total of 96 observations starting from January 2014 to December 2021. The analytical method used in this study isOrdinary Least Square (OLS) using statistical analysis tools 17. The results showed that simultaneously and partially the value of household consumption, state debt and zakat receipts had a positive and significant effect on Indonesia's gross domestic product for the 2014-2021 period with a significance of 0.000. The R-Squared coefficient of determination is 0.9792 or 97.92%.